(untitled) (KYAMC Journal, 2022)
Background: Hepatitis B Virus (HBV) infection is often found in the pediatric population. Virus-related liver diseases are an important cause of morbidity and mortality in Bangladesh. The present study will provide information regarding the seropositivity of HBV infection, risk factors & clinical profile of children suffering from hepatitis. This will ultimately help in early diagnosis and appropriate preventive and curative measures in order to reduce the burden of liver disease in our country. Objective: To ascertain the frequency of Hepatitis B Infection among hospitalized children with acute & chronic liver disease. Materials and Methods: This is a cross-sectional study. A total thirty (30) pediatric patients with acute or chronic liver disease were enrolled in this study. The study was of six months duration from July 2018 to December 2018 in (BSMMU), Paediatric Gastroenterology & Nutrition Department. Children with stigmata of acute & chronic liver disease (ALD /CLD), history of jaundice, and raised ALT level were included and normal ALT level, organomegaly with ascites other than liver disease, patients with acute hepatic failure, suffering from acute hepatitis other than viral infection were excluded. The presence of HBsAg in these patients was detected by (ELISA). In addition to HBsAg, CBC with film, serum bilirubin, prothrombin time , Serum Glutamic Pyruvic Transaminase (SGPT), and serum total protein of each patient was done. Both clinical and laboratory data were collected in a data sheet. Result: Mean age was 8.83 + 4yrs; where all patients were 1 to 14 years age . The male and female ratio was 3.3:1. Non-specific symptoms were Jaundice (76.7%), ascites (50.0%), nausea and vomiting (46.7%) & abdominal pain (40.0%). In this study 76.7% had hepatomegaly and 40.0% had splenomegaly. The Seropositivity rate of HBsAg was found 36.7%. Among all patients of CLD 7 (41.2%) had positive HBsAg and 4 (30.8%) patients of acute ALD had positive HBsAg. Overall Seropositivity rate of HBsAg was found 36.7% of ALD. Conclusion: High seropositivity of HBV in hospitalized pediatric patients which might indicate significant infection among the general pediatric population. KYAMC Journal Vol. 13, No. 03, October 2022: 165-169